Implementation of Good Corporate Governance to Increase Muzakki Loyalty in Zakat Institutions - Zaroni, Akhmad Nur; Iswadi, Muhammad (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The implementation of Good Corporate Governance (GCG) principles in the management of zakat institutions is one of the strategic efforts to increase muzaki loyalty. GCG, which includes the principles of transparency, accountability, responsibility, independence, and fairness, is an important foundation in the management of professional and trustworthy zakat institutions. This study aims to analyze the implementation of GCG and its impact on the level of muzaki loyalty in LAZ DPU East Kalimantan. Using qualitative research methods, data were collected through observation, interviews, and documentation. The results of the study indicate that LAZ DPU has implemented GCG on the principle of transparency in periodic reports, and institutional governance. Accountability is implemented through legal accountability, bookkeeping and recording, and duties and responsibilities. Performance and programs are also recognized in reports and audits. Independence is implemented to maintain integrity and neutrality in distribution, as well as fairness in service. The consistent and optimal implementation of GCG in LAZ DPU East Kalimantan has a positive impact on muzaki loyalty. Increasing trust and positive perceptions of muzaki towards transparent and accountable zakat management are the main factors influencing their loyalty.